Crohn's Disease Presenting with Pyogenic Liver Abscess: A Case Report. (8th August 2012) - McGreal, Sharon; Sayers, Rupert; Wurm, Peter; West, Kevin
Abstract : Pyogenic liver abscess (PLA) is a rare extraintestinal complication of Crohn's disease (CD), and the clinical and laboratory findings may emulate the reactivation of CD, therefore, delaying diagnosis. In this paper the patient presented with PLA as the initial manifestation of CD and experienced severe disease. The finding of PLA was established by computed tomography and initial treatment involved percutaneous drainage and antibiotics. The diagnosis of CD was made after colonoscopy and histological investigations.